Mitochondrial dysfunction in Parkinson disease: evidence in mutant PARK2 fibroblasts - Zanellati, Maria C.; Monti, Valentina; Barzaghi, Chiara; Reale, Chiara; Nardocci, Nardo; Albanese, Alberto; Valente, Enza M.; Ghezzi, Daniele; Garavaglia, Barbara (Frontiers in Genetics, 2015)
Mutations in PARK2, encoding Parkin, cause an autosomal recessive form of juvenile Parkinson Disease (JPD). The aim of the present study was to investigate the impact of PARK2 mutations on mitochondrial function and morphology in human skin fibroblasts. We analyzed cells obtained from four patients clinically characterized by JPD, harboring recessive mutations in PARK2. By quantitative PCR we found a reduction (<50%) of PARK2 transcript in all patients but one; however Western Blot analysis demonstrated the virtual absence of Parkin protein in all mutant fibroblasts. Respiration assays showed an increment of oxygen consumption, which was uncoupled to ATP cellular levels. This finding was probably due to presence of altered mitochondrial membrane potential (ΔΨm), confirmed by JC-1 analysis. The mitochondrial network was comparable between mutant and control cells but, interestingly, a “chain-like” network was found only in mutant fibroblasts. Dissipation of ΔΨm usually leads to mitochondrial fragmentation in healthy cells and eventually to mitophagy; however, this behavior was not observed in patients' fibroblasts. The absence of mitochondrial fragmentation in mutant Parkin fibroblasts could results in accumulation of damaged mitochondria not targeted to mitophagy. This condition should increase the oxidative stress and lead to cellular dysfunction and death. Our results suggest that PARK2 mutations cause mitochondrial impairment, in particular reduction in ATP cellular levels and alteration of ΔΨm, even in non-neuronal cells and confirm the hypothesis that Parkin holds a pivotal role in pro-fission events.